Propuesta para la producción de un abono orgánico partiendo de los lodos residuales de la planta de tratamiento de aguas residuales del Colegio Rochester (2017)
One of the main aims of waste recovery is the minimization of environmental damage and the reuse of any ecological waste in manner which supports the environment and all living beings. The objective of this project is to propose a compost manufacturing process, which utilises sewage sludge produced by Rochester School's wastewater treatment plant. We shall observe and diagnose the physical-chemical, microbiological and quantitative characteristics of the sludge obtained at the end of the drying process, as well as identifying suitable bulking agents (organic wastes, sawdust, and grass clippings). Once the wastes have been diagnosed, the process then corresponds with a selection matrix, which evaluates differents process within different criteria (process time, salubrity, efficiency, available area, and costs). The behaviour of different parameters, such as: temperature, pH, moisture, ash content, and volatile solids, was evaluated during the pre-experimentation (sludge-organic waste-sawdust mix) and experimentation (sludge-organic waste-grass clippings). Furthermore, a scaling up process was developed using the dimensions of the horizontal reactor used in the experiment with the purpose of establish the technical requirements, it’s very important to add that this model is based on the heat generated by the wastes during the composting process. Finally, an analysis of investment and operational costs is carried out, as well as a financial evaluation of the project by a NPV (Net present value).